2019
DOI: 10.1093/ageing/afz136
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality among older people admitted to nursing home

Abstract: Background the increasing number of multimorbid older people places high demands on future health care systems. To inform the discussion on how to structure future care strategies, we aimed to describe the temporal relationship between admission, and morbidity and mortality in nursing home residents. Methods data on 5,179 older individuals admitted to 94 Danish nursing homes in 12 municipalities during 2015–2017 were linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 20 publications
4
43
1
1
Order By: Relevance
“…The Danish study by Reilev and colleagues found that men in NHs have a higher prevalence of comorbidities [15] and shorter survival compared to women, a finding that aligns with our results. As both sexes receive the same type and amount of care in the NH, it is difficult to understand why men have shorter survival in a NH.…”
Section: Survival In Nhssupporting
confidence: 92%
See 1 more Smart Citation
“…The Danish study by Reilev and colleagues found that men in NHs have a higher prevalence of comorbidities [15] and shorter survival compared to women, a finding that aligns with our results. As both sexes receive the same type and amount of care in the NH, it is difficult to understand why men have shorter survival in a NH.…”
Section: Survival In Nhssupporting
confidence: 92%
“…More than 80% of persons living in Norwegian NHs today have dementia [12], and the average length of stay for this group is reported to be 2.4 years [13], similar to figures from the Netherlands [14], where the median length of NH stay for persons with dementia was found to be 2.5 years. Figures on the general NH population in European countries show a mean length of stay of approximately 2 years [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the older adults had to be able to sign an informed consent before the interview. The latter excluded older adults with dementia, which is very common in Danish nursing homes 13 . As such, a limitation to this study is inclusion of residents less frail than expected for older adults with limited life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…The latter excluded older adults with dementia, which is very common in Danish nursing homes. 13 As such, a limitation to this study is inclusion of residents less frail than expected for older adults with limited life expectancy. For these reasons, we believe that in regard to medication, the residents were representative of older adults with a life expectancy of 1-2 years outside nursing home as well.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…International epidemiological research on the health and health care needs of LTCF residents is gaining more attention [48][49][50], allowing for heterogeneity in the care residents' experience to be explored further. Despite the emphasis on ageing in place [51], and a common preference for older adults to remain living in the community until death [52], there is little evidence to suggest that cohorts on admission are in poorer health or have shorter lengths of stay than those in previous years [53].…”
Section: Implications For Future Research Policy and Practicementioning
confidence: 99%